An evaluation of aversive memory and hippocampal oxidative status in streptozotocin-induced diabetic rats treated with resveratrol. (1st January 2017) - Bagatini, Pamela Brambilla; Xavier, Léder Leal; Bertoldi, Karine; Moysés, Felipe; Lovatel, Gisele; Neves, Laura Tartari; Barbosa, Sílvia; Saur, Lisiani; de Senna, Priscylla Nunes; Souto, André Arigony; Siqueira, Ionara Rodrigues; Achaval, Matilde
Highlights: Diabetic rats exhibited normal freezing response in contextual fear conditioning. Hippocampal oxidative status was unaltered in diabetic rats. Resveratrol oral treatment had no significant effects in healthy or diabetic rats. Abstract: The present study evaluated the effects of streptozotocin (STZ)-induced diabetes on aversive memory, free radical content and enzymatic antioxidant activity in the hippocampus of adult Wistar rats submitted to oral treatment with resveratrol. Animals were divided into eight groups: non-diabetic rats treated with saline (ND SAL), non-diabetic rats treated with resveratrol at a dose 5 mg/kg (ND RSV 5), non-diabetic rats treated with resveratrol at a dose 10 mg/kg (ND RSV 10), non-diabetic rats treated with resveratrol at a dose 20 mg/kg (ND RSV 20), diabetic rats treated with saline (D SAL), diabetic rats treated with resveratrol at a dose 5 mg/kg (D RSV 5), diabetic rats treated with resveratrol at a dose 10 mg/kg (D RSV 10) and diabetic rats treated with resveratrol at a dose 20 mg/kg (D RSV 20). The animals received oral gavage for 35 days. The contextual fear conditioning task was performed to evaluate aversive-based learning and memory. The oxidative status was evaluated in the hippocampus, by measuring the free radical content – using a 2′, 7′-dichlorofluorescein diacetate probe – and enzymatic antioxidant activities, such as superoxide dismutase and glutathione peroxidase. Our main behavioral results demonstrated that rats from the D RSV 10 and D RSV 20 groups showed an increase in freezing behavior when compared, respectively, to the ND RSV 10 (p < 0.01) and ND RSV 20 (p < 0.05). Oxidative stress parameters remained unchanged in the hippocampus of all the experimental groups. In contrast to previous experimental findings, our study was unable to detect either cognitive impairments or oxidative stress in the hippocampus of the diabetic rats. We suggest additional long-term investigations be conducted into the temporal pattern of STZ-induced diabetic disruption in memory and hippocampal oxidative status, as well as the effects of resveratrol on these parameters, in a time and dose-dependent manner.